Talent Development Strategies to Enhance Entrepreneurial Orientation among Creative Digital Industry Actors in the Megamas Area of Manado - Kaligis, Jenny Nancy; Rawis, Joulanda Altje Meiske; Tumbelaka, Steven Set Xaverius; Karundeng, Frandy Efraim Fritz (Quantitative Economics and Management Studies, 2025)
This study investigates the impact of talent development strategies on entrepreneurial orientation among actors in the digital creative industry in the Megamas area of Manado, Indonesia. Utilizing a quantitative associative approach, the research analyzes how structured talent initiatives influence entrepreneurial behavior directly and indirectly through digital competence as a mediating variable. Data were collected from 75 digital creative entrepreneurs using a validated Likert-scale questionnaire and analyzed using path analysis with SPSS version 26. The findings reveal that talent development significantly and positively affects both digital competence (β = 0.512, p < 0.001) and entrepreneurial orientation (β = 0.308, p < 0.01). Furthermore, digital competence also has a significant positive effect on entrepreneurial orientation (β = 0.476, p < 0.01), confirming its mediating role. The total effect of talent development on entrepreneurial orientation is strengthened through digital competence, yielding a combined influence of 0.552. These results underscore the importance of aligning talent development programs with efforts to improve digital readiness among creative entrepreneurs. The study contributes to the growing literature on digital entrepreneurship by highlighting the dual impact of talent strategies enhancing both technical and behavioral capabilities. It also provides practical implications for policymakers and stakeholders aiming to empower creative digital MSMEs in emerging markets. In particular, integrating digital skills training with entrepreneurial learning may offer a more comprehensive approach to boosting innovation, risk-taking, and market responsiveness in the creative industry. Future research may explore comparative studies across different urban creative hubs to deepen understanding of regional dynamics in talent-driven entrepreneurship.